Repairs : the added value of being wrong - Brandt, Patrick; Fuss, Eric (Interface explorations ;, 2013)
Grammatical structures connect systems of thought and articulation, the conditions of which hardly seem to fit each other. Repairs are productive mechanisms that solve translation problems between modules or levels by adapting derivations or representations to requirements that have to be met unconditionally. Compensating for derivational and interpretive defects, repairs determine core properties of natural language grammars and their interfaces.